A critical view of female aggression and the implications of gender, culture and a changing society: A Cook Islands perspective. Issue 2 (1st October 2019) - Page, Angela; Te Ava, Aue
AbstractThe form and function of female aggression have been for many years an important social issue that demands investigation. Many studies of female aggression have focused on the perpetration and victimization of girls and young women from western countries. As a result, existing theoretical models and empirical foundations of girls' aggression are based on these defining constructs. The purpose of this article is twofold. The present study of adolescent females in the Cook Islands seeks to understand the role that perpetrators play in the type and the target of aggressive behaviour. It also examines the qualitative findings of girls' aggressive behaviour by boys, girls and their teachers and its gendered relationship inside the Cook Islands environment. The outcomes inspect the cultural context of girls in the Cook Islands that make their understanding and experiences of physical aggression and relational aggression unique and highlight the difficulties of young women positioned themselves between Cook Islands traditional values and asserting their contemporary Cook Islands' identity. The discussion highlights that aggression by girls in the Cook Islands is derived from a particular past and present that can in turn shape understandings of addressing aggression in the future.